The trial [videorecording (Blu-Ray)] - Welles, Orson, 1915-1985; Welles, Orson, 1915-1985; Perkins, Anthony, 1932-1992; Moreau, Jeanne, 1928-2017; Schneider, Romy, 1938-1982; Martinelli, Elsa, 1935-2017; Kafka, Franz, 1883-1924 (Criterion collection, 2023)
A feverishly inspired take on Franz Kafka's novel, Orson Welles₂s film casts Anthony Perkins as the bewildered office drone Josef K., whose arrest for an unspecified crime plunges him into a menacing bureaucratic labyrinth of guilt, corruption, and paranoia. Exiled from Hollywood and creatively unchained, Welles poured his ire at the studio system, McCarthyism, and all forms of totalitarian oppression into this cinematic statement, one of his boldest and most personal, and the film that he himself considered his greatest. Dizzying camera angles, expressionistic lighting, increasingly surreal locations; Welles unleashed the full force of his visual brilliance to convey the nightmarish disorientation of a world gone mad.